Elements of good pharmaceutical practice in the implementation of pharmaceutical care for patients with diabetes during the martial law - I. O. Vlasenko; O. О. Komarida; L. L. Davtian (The State Expert Center of the Ministry of Health of Ukraine, 2022)
During the martial law, the role of pharmacists increases, but they must be educated for such activities. It will ensure pharmaceutical care according to Good Pharmacy Practice. Currently, there are no developed standards for the provision of pharmaceutical care to patients with diabetes mellitus (DM) during the martial law. The purpose of the work is to analyze the legislative changes that took place in the pharmaceutical provision for diabetes patients during the martial law. Recommendations for pharmacists to provide pharmaceutical care to diabetes patients in humanitarian disasters have been developed. The regulatory framework of Ukraine for the provision of diabetes patients and international recommendations for the provision of pharmaceutical assistance to diabetes patients during humanitarian disasters. Content analysis, bibliosemantic, analytical, generalizing analyzes were used. To prevent the consequences of humanitarian disasters for people with diabetes, there must be universal access to insulin, other essential drugs and diagnostics for monitoring of blood glucose level and blood pressure in the conditions of humanitatian crises. The peculiarities of the pharmaceutical supply of patients with diabetes during the martial law have been established. Patients with diabetes in Ukraine can receive insulin and other tableted sugar-reducing drugs in pharmacies, which are reimbursed by medical guarantee program (free of charge or with copayment by the patient), or patients can receive insulin free of charge in regional centers (hospitals) wich were received as humanitarian aid from other countries. The importance to use international gidiline recommendations when receiving drugs as humanitarian aid was underlined. The information about insulin, which are reimbursed now according to the ATC classification, taking into account the duration of action of insulin, has been analyzed and summarized. This information is important for practical use by pharmacists who dispenses insulin according to the newly introduced order (by classification of duration of action of insulin). During the martial law, the role of pharmaceutical workers increases. Recommendations for pharmacists have been developed on the basis of international recommendations and the results of scientific research. These recommendations are appropriate for pharmaceutical care to diabetes patients according to Good Pharmacy Practice during the martial law.